TRAINING FOR LECTURERS AT PTKK IN PRODUCING SCIENTIFIC RESEARCH AND PUBLICATIONS - Junihot M. Simanjuntak (STKIP Citra Bakti, 2024)
This training aimed to enhance the functional position of lecturers by improving their research and publication skills, which in turn contributes significantly to the overall quality of higher education. The program focused on building independent learning capabilities and offering new experiences and knowledge through a qualitative approach utilizing the Research and Development (R&D) model. The primary beneficiaries of this program were 24 lecturers from two higher education institutions (Perguruan Tinggi Keagamaan Kristen - PTKK). The activities included structured training, workshops, and mentoring sessions, employing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results of this program were highly positive: 1) The training model employed proved to be more engaging and effective, significantly enhancing participant interest compared to previous trainings; 2) The research and scientific publications produced by the lecturers saw a substantial increase, indicating the effectiveness of the ADDIE-based training model; 3) Participants demonstrated improved understanding of the critical importance of research and publication in advancing their academic careers, which directly impacts their ability to progress in their functional positions.